Analisis Kelayakan Usaha Budidaya Tanaman Sayuran (Studi Kasus: Petani Sayuran di Kecamatan Landono) - Nurmaya; Harudin, La; Sari, Awal Maulid (Universitas Veteran Bangun Nusantara, 2025)
Landono District is a fertile area with significant potential for agricultural development, including the cultivation of various types of vegetables. The variety of vegetable crops available allows farmers the flexibility to choose the type best suited to their land conditions, resource availability, and market opportunities. However, success in vegetable cultivation depends not only on agronomic aspects but also greatly on the farmer's ability to effectively manage their farming activities, particularly financial management. This study aims to analyze the feasibility of vegetable cultivation carried out by 27 farmers in Landono District. The vegetable farming sector plays a vital role in the economy, but farmers' success depends heavily on efficient business management and a thorough understanding of financial aspects. The data used in this study include detailed production costs (fixed and variable costs) and sales revenues for each farmer. The methodology employed includes descriptive analysis to outline the cost structure, revenue, and profit, as well as a financial feasibility analysis using the R/C (Revenue over Cost) ratio and Break Event Point (BEP). The results indicate that the average production cost structure is dominated by variable costs, particularly for fertilizer, pesticides, and labor. The average net income earned by farmers varies but generally indicates profitability. A feasibility analysis using the R/C ratio indicates that cultivating vegetable crops, including tomatoes, chilies, bitter melon, cucumbers, watermelons, and long beans, in Landono District is feasible with a ratio above 1. Meanwhile, the BEP calculation provides an overview of the minimum production level that must be achieved to cover all costs. These findings provide a basis for farmers to improve business efficiency and for policymakers to design more targeted support programs.